Tindak Tutur Ilokusi Deklaratif, Asertif, Komisif, dan Direktif dalam Berita Acara Pemeriksaan (BAP) Polda Maluku Utara - Mujahid Taha (Madah: Jurnal Bahasa dan Sastra, 2022)
This research aims to reveal and describe illocutionary utterances consisting of declarative, assertive, commissive, and directive illocutions and their perlocutions in a report in the form of minutes of Investigation (BAP) of the North Maluku Regional Police. This research uses data collection and data elaboration methods. This research material is in the form of sentences containing illocutionary and perlocutionary speech acts, namely conveying speech's form, function, and power. The data source in the research was taken from minutes of investigation of the North Maluku Regional Police of 2019-2021. Based on the research findings, it was found: 1. declarative illocutionary forms with the function of naming (labeling) and perlocutionary functions with statements on defamation reports; 2. declarative illocutionary forms with the function of naming (labeling) and perlocutionary forms with the function of statements on defamation reports: 3. assertive illocutionary forms with the function of declaring and perlocutionary with comparative-statement functions on defamation reports; 4. Assertive illocutionary form with the function of stating and perlocutionary with the function of statement-information on a lying news report; 5. commissive illocutionary forms with threatening functions and perlocutions with information-statement functions on reports of threats of violence or intimidation; 6. an illocutionary directive form with a commanding function and a perlocutionary form with a threat-statement function in reports of threats of violence or coercion; 7. commissive illocutionary forms with the function of threatening and promising and perlocutionary with the function of threatening statements on reports of threats of violence or intimidation; 8. commissive illocutionary forms with a threatening function and perlocutionary forms with a threat-statement function on reports of threats of violence or intimidation; and 9. directive and commissive illocutionary forms with suggesting and threatening functions, and perlocutionary forms with information-statement functions.